Emotional Processing of Ironic Versus Literal Criticism in Autistic and Nonautistic Adults: Evidence From Eye‐Tracking. Issue 4 (4th February 2020) - Barzy, Mahsa; Filik, Ruth; Williams, David; Ferguson, Heather J.
Abstract : Typically developing adults are able to keep track of story characters' emotional states online while reading. Filik et al. showed that initially, participants expected the victim to be more hurt by ironic comments than literal, but later considered them less hurtful; ironic comments were regarded as more amusing. We examined these processes in autistic adults, since previous research has demonstrated socio‐emotional difficulties among autistic people, which may lead to problems processing irony and its related emotional processes despite an intact ability to integrate language in context. We recorded eye movements from autistic and nonautistic adults while they read narratives in which a character (the victim) was either criticized in an ironic or a literal manner by another character (the protagonist). A target sentence then either described the victim as feeling hurt/amused by the comment, or the protagonist as having intended to hurt/amused the victim by making the comment. Results from the nonautistic adults broadly replicated the key findings from Filik et al., supporting the two‐stage account. Importantly, the autistic adults did not show comparable two‐stage processing of ironic language; they did not differentiate between the emotional responses for victims or protagonists following ironic versus literal criticism. These findings suggest that autistic people experience a specific difficulty taking into account other peoples' communicative intentions (i.e., infer their mental state) to appropriately anticipate emotional responses to an ironic comment. We discuss how these difficulties might link to atypical socio‐emotional processing in autism, and the ability to maintain successful real‐life social interactions. Autism Res 2020, 13: 563–578 . © 2020 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: In line with research showing that autistic people have difficulties considering others' mental states, we found autistic adults were impaired at distinguishing the emotions and intentions experienced by story characters who received sarcastic comments (e.g., "That was fantastic parking" in a context where someone's parking was particularly bad). These findings highlight the difficulties that autistic people experience taking into account other peoples' intentions during communication to appropriately anticipate their emotional responses. © 2020 International Society for Autism Research, Wiley Periodicals, Inc.